Sustainable Isolation and Application of Rose Petals Based Anthocyanin Natural Dye for Coloration of Bio-Mordanted Wool Fabric: Short title: Dyeing of Bio Mordanted Wool With Rose Petal Extract. Issue 13 (1st December 2022) - Adeel, Shahid; Salman, Mahwish; Usama, Muhammad; Rehman, Fazal-ur-; Ahmad, Tanvir; Amin, Nimra
ABSTRACT: The application of natural dye in the textile industry is gaining popularity because of the increasing awareness of environmental effects, the ecological effects, and the pollution caused by synthetic dyes. Rose flowers, which are one of the best sources of natural dye, have been selected for fabric dyeing due to the presence of anthocyanin pigment. Dyeing of wool is done at optimal conditions such as pH, temperature, time, and salt. It is found that at different percentages (1%, 3%, 5%, 7%, and 9%) chemical and bio mordants mediums gave a variety of shades of good color and better fastness properties onto natural fabrics. By using different chemical and bio mordants and their combinations to analyze the color strength and fastness properties could be enhanced. Bio-mordants gave shades with good color strength and acceptable for the universe. The plant extract has therapeutic values like antioxidant, anti-inflammatory, and antibacterial activity against some gram-positive and gram-negative pathogenic bacteria.